2017
DOI: 10.1177/1367549416682971
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge-making and the media: Genes, genetics, cloning and Mass Observation

Abstract: Copyright and reuse:Sussex Research Online is a digital repository of the research output of the University.Copyright and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable, the material made available in SRO has been checked for eligibility before being made available.Copies of full text items generally can be reproduced, displayed or performed and given to third parties in any format or medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…For example, they can purchase DNA sequencing services to learn about ancestry, discover relatives, and learn about health risks (7)(8)(9). Genetics has also become a more prominent topic in the world news and social media, with these resources often acting as the primary source for public understanding of genetics (10)(11)(12)(13)(14)(15). The COVID-19 pandemic is the most recent example of this, with these sources providing information about the intersection of genetics and personal susceptibility to contracting the virus (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can purchase DNA sequencing services to learn about ancestry, discover relatives, and learn about health risks (7)(8)(9). Genetics has also become a more prominent topic in the world news and social media, with these resources often acting as the primary source for public understanding of genetics (10)(11)(12)(13)(14)(15). The COVID-19 pandemic is the most recent example of this, with these sources providing information about the intersection of genetics and personal susceptibility to contracting the virus (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Parents may find it difficult to communicate openly with their children about the potential impact of a genetic condition, due in part to feelings of guilt . In children and young peoples' broader social context, information about disease, genetics and risk is increasingly present in the media and can influence personal knowledge and misinformation . Several authors have suggested an important role for the school curriculum in ensuring that children receive accurate and developmentally appropriate information about genetics and the associated ethical and legal issues .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the media’s attribute networks of gene editing have always been positively correlated to the government’s attribute networks (see Table 4, Models 1 and 4), regardless of whether the GHB scandal happened. These results render empirical support for the important role of scientists in providing laypeople with the resources they need to form rational perceptions of controversial S&T (Haran & O’Riordan, 2018). Further, these results reveal a feature of online science communication within the Chinese context: Chinese media not only mediates between science and the public (Leydesdorff & Hellsten, 2005), it also observes the government’s agenda on social media closely when representing controversial scientific issues such as gene editing.…”
Section: Discussionmentioning
confidence: 60%